Understanding Youth Political Violence in Nepal. (April 2019) - Shrestha, Ramesh; Jenkins, Bert
Social, economic and political injustice promotes violence among youth. Political parties involved in Nepali democratic upheavals resort to violence; this is where youth are portrayed as major actors in performing violent acts. Youths have always taken part in these political struggles. Political parties have used facts that relate to people suffering from various miseries as a means of manoeuvring and mobilizing youth to participate in armed struggles and uprisings. One would expect these violent episodes to have decreased as the country is now transitioning from armed conflict towards a sustainable peace, but instead post-war Nepal has been continuously facing challenges that youth are posing through their violent behaviours. Addressing issues of unemployment, a corrupt political culture, nepotism and inappropriate political socialization are factors which require urgent responses with political commitment to stop youth participation in political violence. One way to realize this would be to encourage youth engagement in positive peace-building endeavours in Nepal.